Hondered Jaar Kerk en Teologiese Opleiding: 'n Kroniek van die Hervormde Kerk - Oberholzer, J.P (HTS Teologiese Studies / Theological Studies, 2010)
The Faculty of Theology at the University of Pretoria is the oldest university faculty in theology in South Africa. It was founded in 1917 as a multi-ecclesial academic institution, with the Netherdutch Reformed Church of Africa (NRCA) as one of the founding church partners for the scientific training of pastors. However, the initiatives for the establishment of a theological faculty in Pretoria, South Africa are rooted in a synodic resolution of the NRCA in 1909, with the institutionalisation of a Curatorium as an ecclesial executive board responsible for the strategic planning of the Faculty of Theology at the then Transvaal University College, which became the University of Pretoria. In 2009 the NRCA celebrates the centennial anniversary of the Curatorium with the publication of a Chronicle, authored by Professor J.P. Oberholzer. It is published as Supplementum 9 of the HTS Theological Studies, South Africa's oldest theological scholarly journal. The Chronicle consists of 10 chapters: the beginning (1909-1916); the formative stage (1916-1933); multi-ecclesial partnership (1934-1940); internal ecclesial conflict (1941-1953); political tension because of apartheid (1954-1960); ecumenical isolation and internal discord (1961-1970); self-evaluation (1971-1980); growth, retrospection and prospection (1981-1987); rationalisation and optimalisation (1988-1997); multi-ecclesial partnership restored (1998-2009).